Flaky morphology nano zsm-5 molecular sieve, preparation method and application thereof
Patent Information
- Application Number
- CN202411081481.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-08-08
AI Technical Summary
[0005]本发明的目的是提供一种片状形貌纳米ZSM-5分子筛的制备方法,解决了现有技术中片状ZSM-5的制备过程繁琐且产品性质包括形貌和晶粒尺寸不易调控的问题
[0020]本发明片状形貌纳米ZSM-5分子筛的制备方法采用预结晶和晶化相结合的方法,通过在预结晶过程中添加赖氨酸,可有效对片状形貌ZSM-5的b轴厚度和c轴长度进行有效调控,所制备的片状形貌ZSM-5分子筛的平均厚度为20~75nm,平均颗粒尺寸约为0.3~1.5μm,并且其制备方法简单、成本低。
Smart Images

Figure CN118993100B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of molecular sieve synthesis technology, specifically relating to a sheet-like nano ZSM-5 molecular sieve. This invention also relates to the preparation method and application of the above-mentioned molecular sieve. Background Technology
[0002] ZSM-5 molecular sieve is a novel molecular sieve developed by Mobileoil in the 1960s. Its pore system consists of straight channels with a b-axis diameter of 0.56 nm × 0.53 nm and zigzag channels with a b-axis diameter of 0.55 nm × 0.51 nm. In both channel types, the mass transfer path and diffusion barrier are the shortest when molecules pass through along the b-axis. Therefore, compared to traditional ZSM-5 molecular sieves, the short b-axis ZSM-5 molecular sieve has significant advantages in catalytic reactions prone to carbon deposition, especially in methanol aromatization, benzene / ethylene alkylation, and toluene alkylation, showing great potential for industrial application.
[0003] Current preparation techniques include layered silicate exfoliation and hydrothermal synthesis. For example, the prior art in application number CN202310807784.8 introduces dual inhibitors and performs three-stage temperature-controlled crystallization to obtain nanosheet-like ZSM-5 molecular sieves. However, the synthesis method disclosed in this patent is cumbersome, requiring not only the preparation and addition of white liquid seed crystals but also aging and two-stage low-temperature pre-crystallization processes. The prior art in application number CN201710154093.7 uses a method of pre-crystallization at 100-120℃ and crystallization at 140-180℃, using a thin layer of 2-3nm layered, 10-30nm thick two-dimensional crystals as seed crystals, and secondary stacking to form high silica-to-alumina ratio nanosheet-like ZSM-5 molecular sieves with a diameter of 2.0-6.0μm as seed crystals to prepare sheet-like ZSM-5 molecular sieves. Although the above methods can also synthesize nanosheet-like ZSM-5 molecular sieves, these methods have high requirements for seed crystals, and the sheet-like molecular sieves have an aggregated morphology.
[0004] Currently, the layered silicate exfoliation method is costly and complex to synthesize. The high-temperature hydrothermal synthesis method is also complex, sometimes requiring the addition of seed crystals, and the resulting sheet-like ZSM-5 is thick and has an uneven morphology. The low-temperature hydrothermal synthesis method requires a long crystallization time and produces molecular sieves with low crystallinity. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing sheet-like nano ZSM-5 molecular sieves, which solves the problems of cumbersome preparation process and difficulty in controlling product properties, including morphology and grain size, in the prior art.
[0006] The second objective of this invention is to provide a sheet-like nano-ZSM-5 molecular sieve prepared by the above-described preparation method.
[0007] A third objective of this invention is to provide an application of sheet-like nano-ZSM-5 molecular sieves.
[0008] The first technical solution adopted in this invention is a method for preparing sheet-like nano-ZSM-5 molecular sieves, specifically implemented according to the following steps:
[0009] Step 1: Mix the template agent, water, aluminum source and silicon source evenly to form a molecular sieve synthesis mother liquor; Step 2: Add lysine to the molecular sieve synthesis mother liquor and transfer it to a hydrothermal synthesis reactor for pre-crystallization at 50℃~80℃ for 1h~72h.
[0010] Step 3: After pre-crystallization, an inhibitor is added, and crystallization is continued at 150℃~200℃ for 2h~96h. The crystallized product is then separated, dried, and calcined to obtain nano ZSM-5 molecular sieve.
[0011] The first technical solution of the present invention is further characterized in that,
[0012] In step 1, the template agent is one or a mixture of tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetramethylammonium hydroxide, and tetrabutylammonium hydroxide amine; the aluminum source is one or a mixture of sodium aluminate, aluminum isopropoxide, aluminum sulfate, and boehmite; and the silicon source is one or a mixture of tetraethyl orthosilicate, silica sol, and silica.
[0013] In step 1, the molar ratio of silicon source, aluminum source, template agent and water is SiO2:Al2O3:TPAOH:H2O = 50~500:1:10~60:1000~10000, where the number of moles of SiO2 is obtained by converting the number of moles of silicon source to the number of moles of silicon element, and the number of moles of Al2O3 is obtained by converting the number of moles of aluminum source to the number of moles of aluminum element.
[0014] In step 2, the molar ratio of lysine to silicon source is 0.01 to 0.15:1.
[0015] In step 3, the inhibitor is one or a mixture of several of the following: urea, NH4F, (NH4)2CO3, ammonia, ammonium bicarbonate, and ammonium phosphate. The molar ratio of the inhibitor to the silicon source is 0.05 to 0.4:1.
[0016] In step 3, the roasting temperature is 500℃~600℃ and the roasting time is 0.25h~8h.
[0017] The second technical solution adopted in this invention is a sheet-like nano-ZSM-5 molecular sieve.
[0018] The third technical solution adopted in this invention is the application of sheet-like nano ZSM-5 molecular sieves as a bifunctional catalyst in the CO2 hydrogenation reaction.
[0019] The beneficial effects of this invention are:
[0020] The present invention provides a method for preparing sheet-like nano ZSM-5 molecular sieves by combining pre-crystallization and crystallization. By adding lysine during the pre-crystallization process, the b-axis thickness and c-axis length of the sheet-like ZSM-5 can be effectively controlled. The prepared sheet-like ZSM-5 molecular sieves have an average thickness of 20-75 nm and an average particle size of about 0.3-1.5 μm. Furthermore, the preparation method is simple and low in cost.
[0021] A bifunctional catalyst was prepared by mixing sheet-like nano-ZSM-5 molecular sieves with metal composite oxides, pressing, and granulating. When applied to the CO2 hydrogenation to aromatics reaction, it exhibited high activity and aromatic selectivity, and has broad application prospects in CO2 resource utilization. Attached Figure Description
[0022] Figure 1 This is the XRD pattern of the sheet-like nano-ZSM-5 molecular sieve prepared in Example 1 of this invention;
[0023] Figure 2 The image shown is a SEM image of the sheet-like nano-ZSM-5 molecular sieve prepared in Example 1 of this invention.
[0024] Figure 3 The image shown is a SEM image of the sheet-like nano-ZSM-5 molecular sieve prepared in Example 2 of this invention.
[0025] Figure 4 The image shown is a SEM image of the ZSM-5 molecular sieve prepared in Comparative Example 1 of this invention.
[0026] Figure 5 The image shown is a SEM image of the ZSM-5 molecular sieve prepared in Comparative Example 2 of this invention. Detailed Implementation
[0027] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0028] The preparation method of the sheet-like nano ZSM-5 molecular sieve of the present invention is carried out according to the following steps:
[0029] Step 1: Mix the template agent, water, aluminum source and silicon source evenly to form a molecular sieve synthesis mother liquor;
[0030] The template agent is one or a mixture of tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetramethylammonium hydroxide, and tetrabutylammonium hydroxide amine; the aluminum source is one or a mixture of sodium aluminate, aluminum isopropoxide, aluminum sulfate, and boehmite; the silicon source is one or a mixture of tetraethyl orthosilicate, silica sol, and silica.
[0031] Furthermore, the amounts of silicon source, aluminum source, template agent, and water added should be such that the composition and molar ratio of the silica-alumina gel are SiO2:Al2O3:TPAOH:H2O = 50-500:1:10-60:1000-10000, where the number of moles of SiO2 is obtained by converting the number of moles of silicon source into the number of moles of silicon element, and the number of moles of Al2O3 is obtained by converting the number of moles of aluminum source into the number of moles of aluminum element.
[0032] Step 2: After adding lysine to the molecular sieve synthesis mother liquor, transfer it to a hydrothermal synthesis reactor for pre-crystallization at 50℃~80℃ for 1h~72h; the molar ratio of lysine to silicon source SiO2 is 0.01~0.15:1.
[0033] The inhibitor is one or a mixture of several of the following: urea, NH4F, (NH4)2CO3, ammonia, ammonium bicarbonate and ammonium phosphate. The molar ratio of the inhibitor to the silicon source SiO2 is 0.05 to 0.4:1.
[0034] Step 3: After pre-crystallization, an inhibitor is added, and crystallization is continued at 150℃~200℃ for 2h~96h. The crystallized product is then separated, dried, and calcined to obtain nano ZSM-5 molecular sieve.
[0035] The roasting temperature is 500℃~600℃, and the roasting time is 0.25h~8h.
[0036] On the other hand, the present invention also provides a sheet-like morphology nano-ZSM-5 molecular sieve, which is prepared by the above-described preparation method of sheet-like morphology nano-ZSM-5 molecular sieve.
[0037] On the other hand, the present invention also provides the application of sheet-like nano-ZSM-5 molecular sieves as bifunctional catalysts in the CO2 hydrogenation reaction.
[0038] Specifically, the prepared sheet-like nano-ZSM-5 molecular sieve is physically mixed with a metal composite oxide, then pressed into tablets and granulated to obtain a coupled catalyst. The metal composite oxide includes ZnCrO. x ZnAlO x ZnGa2O4, ZnZrO x ZnFeO x One or more of them.
[0039] Example 1
[0040] First, 15g of tetrapropylammonium hydroxide solution, 0.1g of boehmite, 25g of water, and 24g of tetraethyl orthosilicate were weighed and added to 50g of H2O, and stirred. The composition and molar ratio of the molecular sieve synthesis mother liquor were SiO2:Al2O3:TPAOH:H2O = 200:1:31:5520. Next, 1.0g of lysine was weighed and added to the above molecular sieve synthesis mother liquor, and the mixture was stirred overnight at room temperature to evaporate the ethanol. Then, the solution was transferred to a hydrothermal synthesis reactor and pre-crystallized at 70℃ for 24h. After cooling, the molecular sieve precursor solution was obtained. The molar ratio of lysine to SiO2 in the silicon source was 0.06:1. Finally, 2g of urea was added to the above suspension, and the mixture was placed in a reaction vessel and reacted at 180℃ for 24h. The molar ratio of the inhibitor to SiO2 in the silicon source was 0.3:1. The solid product was centrifuged, washed, dried, and calcined to obtain ZSM-5 molecular sieve (named Z5-1).
[0041] Appendix Figure 1 The image shows the XRD pattern of the product obtained in Example 1. It can be seen that the product has the characteristic diffraction peaks of ZSM-5 molecular sieve and has high crystallinity.
[0042] Appendix Figure 2 This is a SEM image of the product obtained in Example 1. The electron microscope image shows that the ZSM-5 molecular sieve has an average thickness of 30–75 nm and an average length along the c-axis of 700 nm, exhibiting a uniform sheet-like nanoparticle morphology.
[0043] Example 2
[0044] First, 15g of tetrapropylammonium hydroxide solution, 0.1g of boehmite, 25g of water, and 24g of tetraethyl orthosilicate were weighed and added to 50g of H2O, and stirred. The composition and molar ratio of the molecular sieve synthesis mother liquor were SiO2:Al2O3:TPAOH:H2O = 200:1:31:5520. Next, 2.0g of lysine was weighed and added to the above molecular sieve synthesis mother liquor, and the mixture was stirred overnight at room temperature to evaporate the ethanol. Then, the solution was transferred to a hydrothermal synthesis reactor and pre-crystallized at 70℃ for 12h. After cooling, the molecular sieve precursor solution was obtained. The molar ratio of lysine to SiO2 in the silicon source was 0.12:1. Finally, 2g of urea was added to the above suspension, and the mixture was placed in a reaction vessel and reacted at 170℃ for 24h. The molar ratio of the inhibitor to SiO2 in the silicon source was 0.30:1. The solid product was centrifuged, washed, dried, and calcined to obtain ZSM-5 molecular sieve (named Z5-2).
[0045] Appendix Figure 3This is a SEM image of the product obtained in Example 2. The electron microscope image shows that the ZSM-5 molecular sieve has an average thickness of approximately 50 nm and an average length along the c-axis of approximately 200 nm, exhibiting a uniform sheet-like nanoparticle morphology with almost no twinning.
[0046] Example 3
[0047] First, 15g of tetrapropylammonium hydroxide solution, 0.1g of boehmite, 25g of water, and 24g of tetraethyl orthosilicate were weighed and added to 50g of H2O, and stirred. The composition and molar ratio of the molecular sieve synthesis mother liquor were SiO2:Al2O3:TPAOH:H2O = 200:1:31:5520. Next, 1.0g of lysine was weighed and added to the above molecular sieve synthesis mother liquor, and the mixture was stirred overnight at room temperature to evaporate the ethanol. Then, the solution was transferred to a hydrothermal synthesis reactor and pre-crystallized at 70℃ for 24h. After cooling, the molecular sieve precursor solution was obtained. The molar ratio of lysine to SiO2 in the silicon source was 0.06:1. Finally, 1g of urea was added to the above suspension, and the mixture was placed in a reaction vessel and reacted at 180℃ for 24h. The molar ratio of the inhibitor to SiO2 in the silicon source was 0.15:1. The solid product was centrifuged, washed, dried, and calcined to obtain ZSM-5 molecular sieve (named Z5-3).
[0048] Example 4
[0049] First, 29g of tetrapropylammonium hydroxide solution, 0.4g of boehmite, 45.5g of water, and 24g of tetraethyl orthosilicate were weighed and added to 100g of H2O, and stirred. The composition and molar ratio of the molecular sieve synthesis mother liquor were SiO2:Al2O3:TPAOH:H2O = 50:1:60:10000. Next, 2.5g of lysine was weighed and added to the above molecular sieve synthesis mother liquor, and the mixture was stirred overnight at room temperature to evaporate the ethanol. Then, the solution was transferred to a hydrothermal synthesis reactor and pre-crystallized at 70℃ for 12h. After cooling, the molecular sieve precursor solution was obtained. The molar ratio of lysine to SiO2 in the silicon source was 0.15:1. Finally, approximately 2.7g of urea was added to the above suspension, and the mixture was placed in a reaction vessel and reacted at 180℃ for 24h. The molar ratio of the inhibitor to SiO2 in the silicon source was 0.4:1. The solid product was centrifuged, washed, dried, and calcined to obtain ZSM-5 molecular sieve (named Z5-4).
[0050] Example 5
[0051] First, 4.8 g of tetrapropylammonium hydroxide solution, 0.04 g of boehmite, and 24 g of tetraethyl orthosilicate were weighed and mixed, and after evaporating approximately 6 g of water, the composition and molar ratio of the molecular sieve synthesis mother liquor were SiO2:Al2O3:TPAOH:H2O = 500:1:10:1000. Next, 1.67 g of lysine was weighed and added to the above molecular sieve synthesis mother liquor, and the mixture was stirred overnight at room temperature to evaporate the ethanol. Then, the solution was transferred to a hydrothermal synthesis reactor and pre-crystallized at 70 °C for 12 h. After cooling, the molecular sieve precursor solution was obtained. The molar ratio of lysine to SiO2 in the silicon source was 0.1:1. Finally, 0.33 g of urea was added to the above suspension, and the mixture was placed in a reaction vessel and reacted at 170 °C for 24 h. The molar ratio of the inhibitor to SiO2 in the silicon source was 0.05:1. The solid product was centrifuged, washed, dried, and calcined to obtain ZSM-5 molecular sieve (named Z5-5).
[0052] Comparative Example 1
[0053] This comparative example provides a method for preparing sheet-like nano-ZSM-5 molecular sieves. The method differs from that in Example 1 in that lysine is not added during the synthesis step; all other methods and steps are the same as in Example 1. Specifically, the preparation method of Comparative Example 1 is as follows: First, 15g of tetrapropylammonium hydroxide solution, 0.1g of boehmite, 25g of water, and 24g of tetraethyl orthosilicate were weighed and added to 50g of H2O, and stirred. The composition and molar ratio of the silica-alumina gel were SiO2:Al2O3:TPAOH:H2O = 200:1:31:5520. Second, the mixture was stirred overnight at room temperature to evaporate the ethanol. Then, the solution was transferred to a hydrothermal synthesis vessel and pre-crystallized at 70°C for 24 hours. After cooling, a molecular sieve precursor solution was obtained. Finally, 2g of urea was added to the suspension, and the mixture was placed in a reaction vessel and reacted at 180°C for 24 hours. The molar ratio of the inhibitor to SiO2 in the silicon source was 0.3:1. The solid product was centrifuged, washed, dried, and calcined to obtain ZSM-5 molecular sieve (named Z5-D1).
[0054] Appendix Figure 4 The results of SEM characterization of the ZSM-5 molecular sieve prepared in this comparative example are shown. The SEM images reveal that the ZSM-5 molecular sieve is relatively thick (>100 nm), with an average grain length along the c-axis >1 μm, indicating a large particle size. Therefore, adding lysine during the pre-crystallization process can effectively control the thickness and grain size of the plate-like ZSM-5 molecular sieve.
[0055] Comparative Example 2
[0056] The ZSM-5 preparation method provided in this comparative example differs from that in Example 1 in that lysine and urea are not added in the synthesis steps, while other methods and steps are the same as in Example 1. Specifically, the preparation method of Comparative Example 2 is as follows: First, 15g of tetrapropylammonium hydroxide solution, 0.1g of boehmite, 25g of water, and 24g of tetraethyl orthosilicate were weighed and added to 50g of H2O, and stirred. The composition and molar ratio of this silica-alumina gel were SiO2:Al2O3:TPAOH:H2O = 200:1:31:5520. Second, 1.0g of lysine was weighed and added to the above molecular sieve mother liquor, and stirred overnight at room temperature to evaporate the ethanol. Then, the above solution was transferred to a hydrothermal synthesis vessel and pre-crystallized at 70℃ for 24h. After cooling, a molecular sieve precursor solution was obtained. The molar ratio of lysine to SiO2 in the silicon source was 0.06:1. Finally, the above mixture was placed in a reaction vessel and reacted at 180℃ for 24h. The solid product was centrifuged, washed, dried, and calcined to obtain ZSM-5 molecular sieve (named Z5-D2). The ZSM-5 molecular sieve prepared in this comparative example was analyzed by SEM.
[0057] Appendix Figure 5 The results of SEM characterization of the ZSM-5 molecular sieve prepared in this comparative example are shown. The SEM images reveal that the ZSM-5 molecular sieve exhibits an irregular spherical morphology, with the spherical particles (60–80 nm) formed by the aggregation of nanocrystals. Therefore, by adding lysine during the pre-crystallization process, the crystallization rate can be accelerated while utilizing its confinement effect to obtain more and smaller ZSM-5 precursor crystals, ultimately resulting in a nanoscale, plate-like ZSM-5 molecular sieve.
[0058] Application Example 1
[0059] This application example provides a method for preparing sheet-like nano-ZSM-5 molecular sieves and its application, wherein the molecular sieves prepared in Examples 1-3 and Comparative Examples 1 and 2 are respectively combined with ZnZrO. x After coupling, it is applied to the catalytic reaction of CO2 hydrogenation to produce aromatics.
[0060] Specifically, the catalytic reaction was carried out in a tubular fixed-bed reactor. 1.0 g of the coupled catalyst was loaded into the middle of a stainless steel tube with an inner diameter of 10 mm. The coupled catalyst was pre-exposed to a pure Ar flow at 0.1 MPa (25 mL / min). -1 The mixture was pretreated at 300℃ for 4 hours, then switched to a mixture of CO2 and hydrogen (volume ratio of CO2 to H2 was 1:3), and subjected to a treatment at 275℃, 1.0 MPa, and 510 mL g. cat -1 h -1The reaction was carried out at space velocity for 24 h. The reaction products were monitored by online gas chromatography. A Shimadzu GC-2014C gas chromatograph equipped with FID was connected to Plot-Q and HP-Pona capillary columns. H2, CH4, N2, CO and CO2 were detected by a Shimadzu GC-2014C gas chromatograph equipped with TCD and TDX-01 columns. The reaction results are shown in Table 1.
[0061] Table 1. Test results of ZSM-5 prepared in Examples 1-3 and Comparative Examples 1 and 2 applied to CO2 hydrogenation reaction.
[0062]
[0063] Among them, C2 = -C4 = This refers to low-carbon olefins (ethylene, propylene, and butene), C2 0 -C4 0 Refers to low-carbon alkanes (ethane, propane, and butane), C 5+ It refers to non-aromatic hydrocarbon compounds containing ≥5 carbon atoms; Aromatic refers to aromatic hydrocarbons.
[0064] As can be seen from the results in Table 1, the metal composite oxide ZnZrO used in this invention... x The bifunctional catalyst prepared by mixing with sheet-like nano ZSM-5 molecular sieve exhibits high CO2 conversion and aromatic selectivity. However, compared with Example 1, the bifunctional catalyst prepared by coupling sheet-like ZSM-5 molecular sieve without lysine with the same metal composite oxide in Comparative Example 1 shows significantly reduced CO2 conversion and aromatic selectivity. The results indicate that the sheet-like nano ZSM-5 molecular sieve prepared in this invention has excellent catalytic performance when combined with oxides and applied to the catalytic reaction of CO2 hydrogenation to aromatics.
Claims
1. A method for preparing sheet-like nano-ZSM-5 molecular sieves, characterized in that, The specific steps are as follows: Step 1: Mix the template agent, water, aluminum source and silicon source evenly to form a molecular sieve synthesis mother liquor; Step 2: After adding lysine to the molecular sieve synthesis mother liquor, transfer it to a hydrothermal synthesis reactor for pre-crystallization at 50℃~80℃ for 1h~72h. Step 3: After pre-crystallization, add inhibitor and continue crystallization at 150℃~200℃ for 2h~96h. Separate, dry and calcine the crystallized product to obtain nano ZSM-5 molecular sieve. In step 2, the molar ratio of lysine to silicon source is 0.01~0.15:1; In step 3, the inhibitor is one or a mixture of several of the following: urea, NH4F, (NH4)2CO3, ammonia, ammonium bicarbonate, and ammonium phosphate. The molar ratio of the inhibitor to the silicon source is 0.05 to 0.4:
1.
2. The method for preparing the sheet-like nano-ZSM-5 molecular sieve according to claim 1, characterized in that, In step 1, the template agent is one or a mixture of tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetramethylammonium hydroxide, and tetrabutylammonium hydroxide; the aluminum source is one or a mixture of sodium aluminate, aluminum isopropoxide, aluminum sulfate, and boehmite; and the silicon source is one or a mixture of tetraethyl orthosilicate, silica sol, and silica.
3. The method for preparing the sheet-like nano-ZSM-5 molecular sieve according to claim 1, characterized in that, In step 1, the molar ratio of silicon source, aluminum source, template agent and water is SiO2:Al2O3:TPAOH:H2O=50~500:1:10~60:1000~10000, where the number of moles of SiO2 is obtained by converting the number of moles of silicon source to the number of moles of silicon element, and the number of moles of Al2O3 is obtained by converting the number of moles of aluminum source to the number of moles of aluminum element.
4. The method for preparing the sheet-like nano-ZSM-5 molecular sieve according to claim 1, characterized in that, In step 3, the roasting temperature is 500℃~600℃, and the roasting time is 0.25h~8h.
5. A sheet-like nano-ZSM-5 molecular sieve, characterized in that, The sheet-like nano-ZSM-5 molecular sieve is prepared by the preparation method of the sheet-like nano-ZSM-5 molecular sieve as described in any one of claims 1 to 4.
6. The application of the sheet-like nano-ZSM-5 molecular sieve of claim 5 in the CO2 hydrogenation reaction, characterized in that, A bifunctional catalyst was prepared by mixing sheet-like nano-ZSM-5 molecular sieves with metal composite oxides, pressing them into tablets, and granulating them. This catalyst was then applied to the CO2 hydrogenation to aromatics reaction.
Citation Information
Patent Citations
A ZSM-5 molecular sieve, a preparing method thereof and applications of the molecular sieve
CN106865566A
Method for preparing nanosheet-shaped zsm-5 molecular sieve and application thereof
CN116854106B